Influence of Parental Support and Achievement Motivation on Academic Performance of Secondary School Islamic Studies Students in Lagos State - Yahya, Isiaq Oluwatosin; Khadijah, Olaniyan-Shobowale; Adekunle, Animashaun Uthman (Journal of Applied Science, Engineering, Technology, and Education, 2022)
This study investigates the influence of parental support and achievement motivation on academic performance of secondary school students in Islamic Religious Studies in Lagos State. The study posed three research questions and tested two hypotheses. The study is a descriptive survey design with the population consisting of all 68 public senior secondary schools in Lagos state Education District V and 31,703 Islamic Religious Studies Students. A Sample of 400 SS II Islamic religious studies students were selected using Simple random sampling technique in 10 randomly selected schools for this study. Descriptive analysis was used to answer the research questions and lineal Regression was used to test hypotheses at α=0.05 level of significance. The study found that the level of Parental Support, Achievement Motivation and Academic Performance were all high among senior secondary schools Islamic Studies Students in Lagos State. Also that Parental Support and Achievement Motivation does not have significant influence on the Academic Performance of senior secondary schools Islamic Studies Students in Lagos State. Based on these findings, it was recommended among others that Parents and guardians should show high level of parental support for their children, in order to reinforce learning and enhance their academic performance.